3, 2/-Dihydroxyflavone-Treated Pluripotent Stem Cells Show Enhanced Proliferation, Pluripotency Marker Expression, and Neuroprotective Properties. Issue 8 (August 2015) - Han, Dawoon; Kim, Han Jun; Choi, Hye Yeon; Kim, Bongwoo; Yang, Gwangmo; Han, Jihae; Dayem, Ahmed Abdal; Lee, Hye-Rim; Kim, Jin Hoi; Lee, Kyung-Mi; Jeong, Kyu-Shik; Do, Sun Hee; et al.
Efficient maintenance of the undifferentiated status of embryonic stem cells (ESCs) may be important for preparation of high-quality cell sources that can be successfully used for stem cell research and therapy. Here we tried to identify a compound that can enhance the quality of pluripotent stem cells. Treatment of ESCs and induced pluripotent stem cells (iPSCs) with 3, 2′-dihydroxyflavone (3, 2′-DHF) led to increases in cell growth, colony formation, and cell proliferation. Treatment with 3, 2′-DHF resulted in high expression of pluripotency markers (OCT4, SOX2, and NANOG) and significant activation (STAT3 and AKT) or suppression (GSK3β and ERK) of self-renewal-related kinases. 3, 2′-DHF-treated high-quality pluripotent stem cells also showed enhanced differentiation potential. In particular, treatment of iPSCs with 3, 2′-DHF led to elevated expression of ectodermal differentiation markers and improved differentiation into fully matured neurons. Next, we investigated the in vivo effect of 3, 2′-DHF-pretreated iPSCs (3, 2′-DHF iPSCs) in a peripheral nerve injury model and found that transplantation of 3, 2′-DHF iPSCs resulted in more efficient axonal regeneration and functional recovery than in controls. Upon histopathological and gene expression analyses, we found that transplantation of 3, 2′-DHF iPSCs stimulated expression of cytokines, such as TNF-α, in the early phase of injury and successfully reduced convalescence time of the injured peripheral nerve, showing an effective neuroprotective property. Taken together, our data suggest that 3, 2′-DHF can be used for more efficient maintenance of pluripotent stem cells as well as for further applications in stem cell research and therapy.